Analisis Peran Pola Asuh Orang Tua terhadap Motivasi Belajar Anak Sekolah Dasar - Mega Silvia Herini; Jingga Febri Yona Malta; Mai Sri Lena; Sartono Sartono (Pedagogi: Jurnal Ilmu Pendidikan, 2023)
This study aims to analyze people's parenting patterns on the learning motivation of elementary school children. With the role of parenting on the learning motivation of elementary school children as a problem formulation. The type of research used is surveys and questionnaires as research instruments to collect data from children's parents. The sample of this study was 152 parents of randomly selected elementary school children. Quantitative descriptive methods are used in this study as a stage in conducting research. Quantitative descriptive analysis as data analysis used in this study. From the survey results, the most commonly used parenting style is democratic parenting. Next is authoritarian parenting and the last is permissive parenting. Upbringing, roles, and parenting styles greatly affect the emergence of children's learning motivation. Generally, parents are more amenable to democratic and authoritarian parenting, because with both parenting styles children want to learn. While parents of elementary school children from the results of many studies disagree regarding permissive parenting because it can make children have less motivation. Keywords: Parenting, Authoritarian, Democratic, Permissive